Biodegradation of polyether-polyol-based polyurethane elastomeric films: influence of partial replacement of polyether polyol by biopolymers of renewable origin - Obruca, Stanislav; Marova, Ivana; Vojtova, Lucy (Environmental technology, 2011)
In this work we investigated the degradation process ofpolyether-polyol-based polyurethane (PUR) elastomeric films in the presence of a mixed thermophilic culture as a model of a natural bacterial consortium. The presence of PUR material in cultivation medium resulted in delayed but intensive growth of the bacterial culture. The unusually long lag phase was caused by the release of unreacted polyether polyol and tin catalyst from the material. The lag phase was significantly shortened and the biodegradability of PUR materials was enhanced by partial replacement (10%) of polyether polyol with biopolymers (carboxymethyl cellulose, hydroxyethyl cellulose, acetyl cellulose and actylated starch). The process of material degradation consisted of two steps. First, the materials were mechanically disrupted and, second, the bacterial culture was able to utilize abiotic degradation products, which resulted in supported bacterial growth. Direct utilization of PUR by the bacterial culture was observed as well, but the bacterial culture contributed only slightly to the total mass losses. The only exception was PUR material modified by acetyl cellulose. In this case, direct biodegradation represented the major mechanism of material decomposition. Moreover, PUR material modified by acetyl cellulose did not tend to undergo abiotic degradation. In conclusion, the modification of PUR by proper biopolymers is a promising strategy for reducing potential negative effects of waste PUR materials on the environment and enhancing their biodegradability.
Keywords: polymery; membrány umělé; Polymers; Elastomers; polyurethany; Biodegradation, Environmental; Conservation of Natural Resources; Membranes, Artificial; Bacterial Physiological Phenomena; Biopolymers; biodegradace; elastomery; biopolymery; Polyurethanes; zachování přírodních zdrojů; fyziologie bakterií